Reading Strategies Employed by Senior High School Students in Understanding Descriptive Texts - T. Wisnu Warnia WR; Selnistia Hidayani; Purnama Rika Perdana (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Reading is a must-have skill for students, regardless of proficiency level. Reading skills are used in all subjects in school. By using reading, they can understand what they learn and obtain information about subjects that help develop their skills. In this term, reading strategies play an important role in defining the success of reading. Many researchers have found that using strategies can help students read effectively and efficiently. This issue is fascinating because success in reading is supported by the strategies readers use. Therefore, the researcher is interested in finding out what reading strategies high school students use. This study aims to examine the reading strategies used by Senior High School students while comprehending descriptive text and their perception of reading strategies. The research design was a qualitative approach based on the theory of case study. The informant consists of tenth-grade students of the eleventh-grade Senior High School. Observation and individual interviews are instruments used by the researcher to collect data, and then the data is analyzed by triangulation, which consists of reducing data, displaying data, and drawing. The results of this study show that there were 7 strategies used by participants namely repeated reading, taking notes, imagine the content, summarizing, bottom up, guessing, getting the purpose of reading, each participant uses more than one strategy in reading, The result also showed that the strategies the students used while reading greatly helped them understand the text and made the reading process more effective and efficient.